Materia Administrativa N° 00596-2011-0-1903-JR-LA-01. Demandante: Martha Esther Reátegui Soria. Demandando: Municipalidad Provincial de Maynas. Materia: Nulidad de Resolución Administrativa. Órgano Jurisdiccional: Juzgado de Trabajo Transitorio de Maynas / Materia Constitucional N° 01962-2014-0-1903-JR-CI-01. Demandante: Christian Paima Campos. Demandando: Electro Oriente S.A. Materia: Hábeas Data. Órgano Jurisdiccional: Primer Juzgado Civil de Maynas - Alván Silvano, Alejandro Samuel Gamaliel (2022)
The present litigation deals with the contentious administrative lawsuit through which Martha Esther Reátegui Soria requested the restitution of the right to work and reinstatement to her job, because the Public Entity of the Provincial Municipality of Maynas arbitrarily fired her by preventing her from entering her work center as Promoter in the Glass of Milk Program. In the judgment of first and second instance issued by the A quo and the Ad quem respectively, they considered that there was no violation of the constitutional right to work because the plaintiff was under the rule of the CAS and one of the grounds for termination was the expiry of the hiring period and it was not necessary to hire her again. However, in the cassation procedure filed by the plaintiff, the First Chamber of Transitory Constitutional and Social Law of the Supreme Court of Justice of the Republic, declared the lawsuit founded in which it is established as decision-making grounds that it was appropriate to protect what was requested by the plaintiff because the right to work was violated and the distortion of the protected contract and the guiding principles of labor and constitutional law were not taken into account.